Exploration of mothers' experiences of having a child with down's syndrome and their quality of life : a mixed method study / Chan Kim Geok - Chan, Kim Geok (2012)
Mothers of child with the unexpected diagnosis of Down’s syndrome (DS) were reported to be dealing with an on-going, chronic situation in supporting their child’s various needs throughout their life. They were reported to perceive lower quality of life. There are little published studies related to experiences of mothers in Malaysia, particularly in the Borneo state of Sarawak with its diverse socio-economic, cultural and geographical background. The effects of having a child with DS on the quality of life (QOL) of mothers are little known. The purpose of the study is to understand the experiences of mothers having a child with DS and their QOL in the local context. It also aims to examine the relationship between mothers’ selected background variables and their perceived QOL. Parallel mixed research design approach was utilized. Qualitative interviews were conducted to explore the experiences of 26 biological mothers of child having DS aged ≤ 18 years old. QOL of another 161 biological mothers were assessed using the WHOQOL-BREF. These mothers were all accessed from the various institutions which provide interventional or educational programs for children with disabilities. These institutions were located within and nearby the capital city of Kuching and the rural region of Samarahan Division within the Borneo state of Malaysia (Sarawak). Audio-recorded interviews were transcribed and analyzed thematically. Quantitative data analysis was done using Statistical Package for Social Sciences 19.0. Mothers’ experiences were represented in the five major themes and subthemes which emerged, namely the various emotions, extra care demands, variation of supports, coping strategies and life impacts. Experiences of positive life impacts of competence and growth, joy of parenting and excitement with child’s development were evident though there were worries and extra care demands. The outcomes of mothering a child with DS are not completely negative among mothers, though this could be related to their accessibility to family resources of various sources of supports and coping strategies. An overall QOL mean score of 14.0 ± 1.84 was obtained. The relatively lower mean score for QOL of environmental supports domain (mean=13.3±2.1) indicates the existence and extent of gap in relation to their experience of difficulty in their access to environmental support in meeting the needs for care giving of their child. Selected background variables (locality, education and income levels, marital status) were significantly correlated with their perceived overall QOL, with rho (161) = 0.22 to 0.28 (p<0.01). Maternal age was found to be inversely correlated with their overall and QOL of physical health domain. Regression analysis shows that rural-urban locality, education and income levels, marital status and maternal age together accounted for 14.5% of the variance in the sample’s QOL score. Mothers who have a lower education and income levels, living in the rural locality, older in age and as singles are more likely to perceive poorer overall QOL. Various recommendations for care professionals in their practice, policy, education and future research are presented.